2016
DOI: 10.1136/bmjopen-2015-010875
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of patients with type 2 diabetes in OR Tambo district, South Africa

Abstract: ObjectivesSouth Africa has pledged to the sustainable development goal of promoting good health and well-being to all residents. While this is laudable, paucity of reliable epidemiological data for different regions on diabetes and treatment outcomes may further widen the inequalities of access and quality of healthcare services across the country. This study examines the sociodemographic and clinical determinants of uncontrolled type 2 diabetes mellitus (T2DM) in individuals attending primary healthcare in OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 29 publications
(43 reference statements)
10
43
2
Order By: Relevance
“…The possible explanation for this are factors such as the timing of initiation of insulin and insulin regimen schedules. This phenomenon has also been reported elsewhere [56,57 ], and we will again be looking at this further in future research projects.…”
Section: Discussionsupporting
confidence: 84%
“…The possible explanation for this are factors such as the timing of initiation of insulin and insulin regimen schedules. This phenomenon has also been reported elsewhere [56,57 ], and we will again be looking at this further in future research projects.…”
Section: Discussionsupporting
confidence: 84%
“…The result of this study showed that the level of glycemic control among type II diabetic patients is 71.4% which is consistent with the finding at Dessie Referral Hospital (70.8%), Jimma University Teaching Hospital (70.9%), Turkey (67.5), Myanmar (72.1%), and Saudi Arabia (74.9%) [ 12 , 20 , [30] , [31] , [32] ]. On the other hand, it is below than the study conducted at Tikur Anbessa Hospital (80%), South Africa (83.8%), Kenya (81.6%), India (91.8%), and Palestine (80.5%) [ [33] , [34] , [35] , [36] , [37] ]. On the other hand, it is higher than the study done at Zambia (61.3%), Limmu Genet Hospital (63.8%), Suhul Hospital (63.5%), Nigeria (55%), Ayider Specialized hospital (48.7%) and Shenen Gibe Hospital (59.2%) [ 21 , [38] , [39] , [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 80%
“…It was found that the duration of HIV infection, large abdominal circumference, 19 overweight/obesity, sedentary living, low income and lack of information were contributing factors for developing dysglycemia in African populations. 23 Higher baseline HIV 1 RNA and body mass index (BMI) were also established to be associated with greater risks. 24 Surprisingly, Tzur et al found that HIV-infected Ethiopians are more likely to develop DM at low BMI values compared to non-Ethiopians.…”
Section: Methodsmentioning
confidence: 99%